Prevention and criminal offences in university education in the face of artificial intelligence: Regulatory framework, institutional response and challenges of the European AI Act - Giner Alegría, César Augusto (Cuadernos de RES PUBLICA en derecho y criminología, 2026)
The integration of artificial intelligence (AI) into university education has profoundly transformed teaching and assessment methods, while simultaneously opening new avenues for the commission of criminal offences. This article analyses the types of offences facilitated by AI in academia — automated plagiarism, identity theft, document forgery, fraud in automated assessments and production of illegal content — and examines in depth the applicable regulatory framework, with particular attention to Regulation (EU) 2024/1689 on Artificial Intelligence (AI Act) and its direct implications for higher education institutions. It also analyses the most effective prevention and institutional response strategies, identifying the existing gaps between technological reality and current normative and organisational capacities. The methodology is qualitative and exploratory, based on systematic literature review, documentary analysis of the AI Act and semi-structured expert interviews. The findings reveal a progressive increase in these offences, the insufficiency of the pre-existing legal framework and the urgent need for robust institutional policies that articulate prevention, digital ethics training and academic compliance mechanisms . This article aims to systematise the landscape of AI-facilitated criminal offences in the Spanish and European university context, analyse in depth the implications of the AI Act for educational institutions, and propose a model of institutional response that integrates prevention, detection, sanction and a culture of integrity. To this end, an interdisciplinary perspective is adopted that integrates criminal law, criminology, applied ethics and educational technology studies.